Green Tourism Regulation on Sustainable Development: Droning from Indonesia and China - Jaelani, Abdul Kadir; Hayat, Muhammad Jihadul; Luthviati, Resti Dian; Al-Fatih, Sholahuddin; Mujib, M. Misbahul (Journal of Indonesian Legal Studies, 2023)
For more than five decades (since 1972), the world has increasingly directed its attention toward sustainable development, one of which encompasses the domain of green tourism. Indonesia and China stand as two nations committed to the Sustainable Development Goals and green tourism. Nevertheless, it remains uncertain whether the legal framework on green tourism in both countries has achieved comprehensiveness and the extent of its implementation's effectiveness. This article aims to explore the regulations on green tourism in Indonesia and China, along with their respective impacts. Drawing on a statute approach, this article argues that Indonesia has established multiple levels of regulations concerning green tourism as a part of its commitment to sustainable development and China. In practice, both Indonesia and China have implemented these regulations, leading to discernible positive effects on societal welfare. However, conventional regulatory overlap persists in Indonesia, and the implementation appears less than optimal. In another context, China adopts a streamlined regulatory framework and appears to have achieved greater effectiveness in the implementation of green tourism.